2015
DOI: 10.1111/febs.13279
|View full text |Cite|
|
Sign up to set email alerts
|

Bone marrow‐specific caspase‐1/11 deficiency inhibits atherosclerosis development in Ldlr−/− mice

Abstract: Recent investigations have suggested that inflammasome activation plays an important role during atherosclerosis. Upon activation, the inflammasome induces processing and release of pro‐inflammatory cytokines interleukin 1β (IL‐1β) and interleukin 18 (IL‐18) via activation of caspase‐1/11. Previously, it was shown that complete caspase‐1 deficiency is protective against atherosclerosis development. However, while macrophages are the main inflammatory cells involved in atherosclerosis, the exact role of macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 37 publications
(55 reference statements)
0
39
0
Order By: Relevance
“…Bone marrow-derived macrophages (BMDMs) were isolated as described previously26. Cells were grown in 12-well plates (Greiner Bio-One) on coverslips (Ø 20 mm; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMDMs) were isolated as described previously26. Cells were grown in 12-well plates (Greiner Bio-One) on coverslips (Ø 20 mm; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, NLR pyrin domain containing 3 (NLRP3), a member of the NLR family, recognizes various DAMPs to form an NLRP3 inflammasome molecular complex in the cytosol and leads to inflammatory responses. Indeed, recent studies demonstrated that NLRP3 inflammasome-driven inflammatory responses contributed to the progression of atherosclerosis 1013) . This study highlighted the present state of knowledge on the role of NLRP3 inflammasomes in the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the lipid core within the plaque improves plaque stability [72]. Also, specifically silencing mouse bone marrow caspase-1/11 gene can significantly reduce the necrotic lipid core of plaque and enhance plaque stability [81]. Studies have found that MCC950, an NLRP3 inflammation inhibitor, can significantly improve the stability of mouse platelets because it inhibits the inflammatory response of macrophages [82].…”
Section: Nlrp3 Inflammasome Andmentioning
confidence: 99%